Physicochemical Analysis of Chloride Diffusion and Adsorption in Water-saturated Concrete: Theory and Measurement - Ichikawa, Tsuneki; Haga, Kazuko; Yamada, Kazuo (Journal of advanced concrete technology, 2023)
The theory of ionic diffusion in water-saturated concrete accompanying ion exchange with mobile or immobile adsorbed ions was constructed by using the general theory of diffusion and the condition of electrical neutrality. Analysis of the diffusion profile of chloride (Cl−) ions in concrete with the theory revealed that adsorbed Cl− ions in AFm and C-S-H are as mobile as free Cl− ions in the pore solution, so that the adsorption does not retard the ingress of Cl− ions. The existing test methods for determining the effective or apparent diffusion coefficient of Cl− ions were evaluated on the bases of the present theory and new experimental findings. It was revealed that steady-state electrochemical methods such as NTBUILD-355 and ASTM C1202 are not suitable for determining the diffusion coefficient, because the steady state methods expel preexisting diffusible ions which strongly affect the diffusion of Cl− ions. Moreover, the steady state methods overestimate the diffusion rate because the methods assume that adsorbed Cl− ions are immobile. The electrochemically-accelerated method NT BUILD 443 is also unsuitable for the diffusion test, because the acceleration is induced by the electro-osmotic flow of the external solution into concrete. The present diffusion theory necessitates the effective self-diffusion coefficient of not only Cl− ions but also all the other diffusible ions in concrete. A simple method of determining the effective self-diffusion coefficients of arbitrary ions in concrete from the diffusion profile of Cl− ions was presented.